Deixis in Traditional Wedding Ceremony ``Mangambat Boru'' of Mandailing - ., Khairunnisah; Siagian, Abdul Rahman; Sri Rezeki Purba, Happy; Sari Hasibuan, Nikmah (KnE Social Sciences, 2023)
This study attempted to describe the various deixis contained in traditional wedding ceremony ”mangambat boru”of Mandailing. The problems in this study are: 1) what types of deixis are there in traditional wedding ceremony”mangambat boru”of Mandailing ; 2) what is the functions of the deixis uses in traditional wedding ceremony”mangambat boru”of Mandailing. The purposes are going to be achieved by this study are such as: 1) to describe the various types of deixis, 2) to describe the function of the deixis were used.The subject of this researchwas thetraditional wedding ceremony”mangambat boru”of Mandailingwhich consist six wedding in Panyabungan. The data in this study are: words, phrases, sentences, using Mandailing Language.Furthermore, there are four kinds of deixis used in traditional wedding ceremony”mangambat boru”of Mandailing, which consists of deixis place, deixis time,deixis demonstratif, and deixis persona. Based on this research then the number of data were 180words deixis, the most frequently used was person deixis with 120 words. On theorder of second was demonstratif deixis with 30 words . In the third sequence spatial deixis with theamount of data that found as many as 20words, and the last temporal deixis was 10 words. Keywords: Wedding ceremony; Deixis; traditional; Mangambat Boru